Fermentation of Sago Pulp using Pleurotus Ostreatus on Dry Matter, Protein and Crude Fiber Content - Moningkey, Sonny A.E; Anis, Selvie D.; Imbar, Meity R.; Bagau, Betty; Wolayan, Feny; Regar, Mursye N. (Jambura Journal of Animal Science, 2025)
This study aims to determine the effect of the fermentation time of sago pulp using white oyster mushrooms (Pleurotus ostreatus) on the content of dry matter, protein and crude fiber. Field research has been conducted in Tomohon city and the results of the study were analyzed at the Food and Non-Food Sample Testing Laboratory, Manado Industrial Standardization and Service Center. This study used a Completely Randomized Design (CRD) consisting of 4 treatments and 5 replications. The treatment design is P0 = Fermentation Time 0 days; P1 = Fermentation Time 2 weeks; P2 = Fermentation Time 4 weeks and P3 = Fermentation Time 6 weeks. The variables measured in this study were dry matter, protein and crude fiber content. The results of the diversity analysis showed that the treatment of sago pulp fermentation time using white oyster mushrooms (Pleurotus ostreatus) showed very significant different results (P 0.01) on the dry matter and protein content. The average value of dry matter for each treatment obtained was P0 = 44.94%; P1=44.94%; P2=46.54% and P3=46.96%, while the average protein value is P0=3.32%; P1=3.36%; P2=5.29% and P3=4.99%. Analysis of diversity shows that the treatment gives a response to the crude fiber content showing no significant difference (P0.05) with an average value of each treatment, namely P0=22.22%; P1=21.62%; P2=18.53% and P3=18.84%. The results of the study showed that the treatment of sago pulp fermentation for 4 weeks using white oyster mushrooms (Pleorotus ostreatus) showed the best results in terms of dry matter and protein content